Does Soil Structure Influence Phosphorus Availability in Andosols? - Clunes, John; Werner-Auad, Sadi; Bustos-Korts, Daniela; Zúñiga-Ugalde, Felipe (REVISTA TERRA LATINOAMERICANA, 2025)
Phosphorus (P) availability in the soil is a limiting nutrient for biomass production in agroecosystems developed in Andosols. Nonetheless, it remains unknown how soil structure af fects the storage and availability of this nutrient. Thus, this research aimed to evaluate the role of soil structure in phosphorus availability using Olsen P as a chemical indicator of availability. Undisturbed and disturbed soil samples were collected following a grid pattern under naturalized and sowed pastures that reflected two dif ferent soil structures (untilled and tilled, respectively). The untilled soil showed higher variability and a higher concentration of Olsen P (5-27 mg kg-1) than the tilled soil (14 mg kg-1). Undisturbed samples collected in cylinders showed that Olsen P continues to increase af ter removing the soil from the cylinder, sieving the sample, and re-extracting Olsen P, resulting in three times the amount of Olsen P found in disturbed samples collected before the experiment. The methodological approach used in this research allowed to highlight the role that soil structure plays in the availability of P over time to improve the ef ficiency of nutrient utilization.